A ruptured penetrating atherosclerotic ulcer of the ascending aorta: a case report of an endovascular repair with extending the length of the aortic coverage by debranching the innominate artery. Issue 2 (27th April 2019) - Chenesseau, Josephine; Barral, Pierre-Antoine; Piquet, Philippe; Gaudry, Marine
Abstract: Background: An endovascular approach to the management of a ruptured plaque in the ascending aorta may be an alternative to open surgery in high-risk patients. This option may become inevitable due to the number of elderly patients unfit for open cardiac surgery. There are very few stent grafts able to fit the ascending aorta and in emergency cases, most medical teams have been limited to current thoracic aortic endografts, the shortest of which measure 10 cm. Case summary: We report a case of an endovascular repair of a ruptured penetrating atherosclerotic ulcer of the ascending aorta. The patient was considered for open cardiac surgery but was evaluated at a high mortality risk based on his age, his medical history, and significant calcifications on his aorta. Our vascular surgical team decided then to perform an endovascular repair with extending the length of the aortic coverage by debranching the innominate artery. Discussion: Endovascular treatment of an acute ruptured aorta is feasible in high-risk patients with thoracic endovascular stent grafts and coverage of the innominate artery. Endovascular treatment of the ascending aorta is at its infancy and in need of further research. New stent grafts designed for the ascending aorta are in progress and should increase the numbers of interventions in the years to come.